The relative risks, and the likelihoods, of becoming postnatally distressed in the presence of common psychosocial risks: a study with Italian-speaking mothers. Issue 5 (19th October 2016) - Della Vedova, Anna M.; Matthey, Stephen
Abstract: Several psychosocial risk factors have been consistently identified for postnatal distress in women, including lack of support, a personal or family history of depression, and recent stressful life events. Studies usually emphasize the statistical nature of these risks, without focusing on their clinical significance, which is important to aid in the communication with expectant couples. Four hundred and sixteen Italian-speaking women attending public health services completed measures, assessing current distress and psychosocial risk variables, at 2–3 months postpartum. Logistic regression, together with the strength of the obtained statistics, is reported. A personal history of depressed mood, stressful events, and conflict with her partner in the past year were risks of at least moderate size, though only for the last variable were half or more of the women with the risk likely to experience distress. A family history of mood disorders was no longer a risk once the woman's personal history was taken into account. Furthermore between a quarter to a third of women lacking current social support experienced distress. Understanding the strength of these risks, and the frequency with which they are associated with postpartum distress, will help clinicians communicate the implications of such risks to couples.